So long at the fair - Irwin, Hadley (M.K. McElderry Books, 1988)
The summer fairgrounds provide a temporary refuge for eighteen-year-old Joel as he struggles to deal with his memories of Ashley, the friend he loved and expected to have as a part of his life always.